COVID-19 vaccination in advanced skin cancer patients receiving systemic anticancer treatment: A prospective singlecenter study investigating seroconversion rates - Lodde, Georg C.; Fiedler, Melanie; Dittmer, Ulf; Placke, Jan-Malte; Jansen, Philipp; Becker, Jürgen C.; Zimmer, Lisa; Livingstone, Elisabeth; Schadendorf, Dirk; Sondermann, Wiebke; Ugurel, Selma (Frontiers in Oncology, 2022)
Background: COVID-19 vaccination reduces risk of SARS-CoV-2 infection, COVID-19 severity and death. However, COVID-19 vaccination in cancer patients requiring systemic anticancer treatment is poorly investigated. The aim of the present study was to determine the efficacy of COVID-19 vaccination in advanced skin cancer patients under active systemic anticancer treatment. Methods: In this prospective, single-center, cohort study from May 2020 until October 2021, 60 patients with systemic treatment for advanced skin cancer, known COVID-19 vaccination status and repetitive anti–SARS-CoV-2-S IgG serum quantification were enrolled. Thereof, 41 patients received complete COVID-19 vaccination. Median follow-up time was 12.7 months. Results: Of 60 patients with advanced skin cancers, 52 patients (86.7%) received immune checkpoint inhibition (ICI), seven (11.7%) targeted agents (TT), one (1.7%) chemotherapy. 41 patients completed COVID-19 vaccination with two doses during study progress. Of those, serum testing revealed n=3 patients (7.3%) as anti-SARS-CoV-2-S IgG positive prior to vaccination, n=32 patients (78.0%) showed a seroconversion, n=6 patients (14.6%) did not achieve a seroconversion. Patients failing serological response were immunocompromised due to concomitant hematological malignancy, previous chemotherapy or autoimmune disease requiring immunosuppressive comedications. Immunosuppressive comedication due to severe adverse events of ICI therapy did not impaired seroconversion following COVID-19 vaccination. Conclusion and Relevance: COVID-19 vaccination is effective in advanced skin cancer patients under systemic anticancer treatment. An impaired serological response was observed in patients who were immunocompromised due to concomitant diseases or previous chemotherapies. Immunosuppressive comedication due to severe adverse events of ICI did not impair the serological response to COVID-19 vaccination.